Identifying challenges facing manufacturing enterprises toward implementing sustainability in newly industrialized countries. Issue 7 (4th September 2017) - Garbie, Ibrahim
Abstract : Purpose: The purpose of this paper is to present and identify the challenges toward implementing sustainability strategies both strategic and tactical (STs) and performance measures (PMs) facing industrial organizations in newly industrialized countries. Design/methodology/approach: Conducting a comprehensive survey on the published papers focused on the area of sustainability and/or sustainable development (S/SD) in manufacturing enterprises to identify the most common critical challenges. Setting with industrialists to determine which challenges the industrial organizations facing while implementing the S/SD strategies in terms of strategic, tactic and PMs. Using support logic techniques such as interpretive structural modeling (ISM) and interpretive ranking process (IRP) as modeling approaches to examine the contextual relationship among the STs and PMs individually "first phase, " to clarify and identify the most and least dominant factors, and to rank STs with respect to the PMs "second phase." Findings: The investigation shows that some challenges are more dominant and influential. Literacy and an awareness of sustainability, globalization and international issues and competitive strategies have emerged as the most dominant and key driving factors for STs in the ISM model, while the whole PMs are driven by remanufacturing and recycling factors in the ISM model. In addition, drivers and barriers to implementing S/SD challenges received the highest rank in the IRP model. Research limitations/implications: Most of the STs and PMs were identified from academicians. Most of the manufacturing companies participated in the discussion; unfortunately, all are not familiar with the S/SD as a whole. They see to the S/SD from very narrow scope like climate change, environmental and energy issues only based on what they heard from media. Most of them are not fully interested to join with academicians to progress the work. Practical implications: Most of the manufacturing companies are keen to investigate extremely sustainability challenges. Although this paper has a goal to provide a comprehensive framework to analyze, investigate and model sustainability challenges for industrial/manufacturing companies in different industrial sectors, most of the STs and PMs were identified from academicians. Most of the industrial/manufacturing companies participated in the discussion; unfortunately, all are not familiar with the S/SD as a whole. This study will help manufacturing/industrial companies to analyze and investigate the challenges toward implementing S/SD. Originality/value: The originality of this paper is to identify the most common ST and PM challenges facing industrial organization toward implementing S/SD, modeling them into logical techniques and comparing between STs with respect to PMs.